Chapter Sobre el papel de Lope de Vega en la construcción del relato nacional del clasicismo francés (Studi e saggi, 2020)
This essay deals with an aspect of the formation process of the image of the Spanish Baroque theatre in France as an irregular and chaotic aesthetic form, which was also considered inferior with respect to the French classical model. In this theoretical construction, Lope de Vega embodies all of the Spanish theatre's flaws and, more generally, Hispanic literature's ones, in turn conceived as an expression of the Spanish nation's spirit. This process of elaborating an image of an author at the service of the invention of a national stereotype is possible thanks to the early reception of some prose works by Lope (La Arcadia, El peregrino en su patria) which are enjoying a widespread diffusion in their translations. In a context marked by controversy surrounding the tragi-comédie, assimilated by his detractors to a simple theatrical deformation of novelistic material, Lope de Vega assumes the function of representative of a literature considered extraneous to any rule and to the separation between literary genres.